Aquatic"“terrestrial trophic linkages via riverine invertebrates in a South African catchment - Moyo, Sydney (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
Rivers play a vital role in human livelihoods and are likely to undergo substantial alteration due to climate and land use changes from an increasing human population. Mitigating the pressures facing rivers in the world requires scientists and environmental managers to understand the ecological mechanisms, and ultimately the strength, of connections between ecosystems. This understanding of connections between adjacent habitats will enable environmental managers to predict the consequences of perturbing these linkages in the future. In this thesis, aquatic-terrestrial linkages in rivers were investigated using ecologically meaningful variables including abundances, biomasses, stable isotopes and fatty acids. This study is part of a larger project entitled "Connectivity through allochthony: reciprocal links between adjacent aquatic and terrestrial ecosystems in South Africa" , in which a team of researchers assessed a variety of pathways connecting riverine and estuarine systems to land within a catchment in the Eastern Cape, South Africa. I conceptualised the flow of energy within a temperate southern hemisphere river (the Kowie River) within theoretical models of energy flow such as the River Continuum Concept (RCC; presents lotic systems as being longitudinally linked with food webs in shaded headwaters being principally driven by allochthonous energy, with the addition of autochthonous food as a minor carbon source in the lower reaches) and the Riverine Productivity Model (RPM; proposes consumers derive most of their energy from local production of phytoplankton, benthic algae and aquatic plants, as well as directly from riparian zones via terrestrial leaf litter). Using the RCC as a starting point, I collected macroinvertebrates (September 2012 to May 2013) along a longitudinal gradient and grouped them into functional feeding groups (FFGs). The results revealed that gatherers and filterers dominated in the Kowie River, and together represented 50 "“ 83% of the invertebrate assemblages. There was a general paucity of shredders (relative abundance was â‰¤ 10% across all sites and seasons). The changes in relative abundances of different FFGs did not follow predictions of the RCC along the longitudinal gradient, as there were no correlations of community structure with some physical attributes (stream width, canopy cover, distance of river) that changed along the river continuum. However, FFG abundances were related to water velocity, total dissolved solids and canopy cover. Broadly, the Kowie River data showed that changes in relative abundances of FFGs along the river continuum could not be explained by changes in physical attributes alone, and may be highly influenced by the availability of food and the chemistry of the stream. Analysis of stable carbon (Î´13C) and nitrogen (Î´15N) isotopes was used to estimate the contributions of algal and land-based production to consumers over space (six sites) and time (November 2012 to September 2013). Carbon contributions determined by the use of mixing models (Stable Isotope Analysis in R) revealed that consumers in the headwater assimilated mainly terrestrially-derived organic matter, with consumers in the middle and lower reaches assimilating autochthonous basal resources (macrophytes and algae). The findings from this river supported aspects of the RCC (at the headwaters; terrestrial organic matter made up 41% of consumer diets), but overall the data supported the predictions of the RPM (local production made the highest contributions of 50 "“ 86% to all FFGs across all seasons). The carbon isotopes of consumers and their food sources changed substantially every season, indicating that samples of food sources and consumers should be analysed many times throughout the year to capture that variability and to ensure that ephemeral components of the food web are not missed. To validate the findings from the isotope data, fatty acids were used as complementary tracers to determine the contributions of algal versus terrestrial organic matter to the consumers. Fatty acid tracers for terrestrial (Æ©Ï‰3/Æ©Ï‰6; 18:2Ï‰6; 18:3Ï‰3) vs aquatic (Æ©Ï‰3/Æ©Ï‰6; 20:5Ï‰3) sources corroborated the findings from the isotope data set, as the mean ratio of Æ©Ï‰3/Æ©Ï‰6 in consumers was less than one at the headwaters (indicating allochthony), while middle and lower reaches were associated with Æ©Ï‰3/Æ©Ï‰6 > 1 (indicating autochthony). In addition to the tracer and FFG analyses for examining trophic connections between land and river, the bidirectional exchange of organisms between the riparian zone and the river was assessed using floating pyramidal traps (to measure emergence) and pan traps (for infalling invertebrates) placed at different sites in the river and the biomass in each trap was determined. The exchanges were variable over space and time, with emergence peaking in summer (169 to 1402 mg m-2 day-1) and declining in winter (3 to 28 mg m-2 day-1). Similarly, infalling invertebrates increased in summer (413 to 679 mg m-2 day-1) and declined in winter (11 to 220 mg m-2 day-1). Biomass measurements are indications of quantity that ignore nutritional quality, so I determined the bidirectional flow of invertebrates using absolute concentrations of physiologically important biochemical compounds (essential and polyunsaturated fatty acids). The fluxes of emergent and infalling arthropods peaked in summer (emergence = 0.3 to 18 mg m-2 day-1 and terrestrial infall = 0.3 to 3 mg m-2 day-1) and declined in winter (emergence = 0.01 to 0.51 mg m-2 day-1 and terrestrial infall = 0.01 to 0.03 mg m-2 day-1). However, during some seasons, no significant differences in polyunsaturated fatty acid flux in either direction were observed; this finding indicated the balance of reciprocal subsidisation via reciprocal flows of animals. Factors such as air temperature and algal productivity affected the reciprocal flows between adjacent habitats, with algal productivity being positively related to emergence while air temperature was positively correlated to infalling terrestrial invertebrates. This research enhances the growing body of literature on the function of riverine systems and offers some invaluable information on the flow of energy and the role played by invertebrates in translocating nutrients from terrestrial systems to aquatic systems and vice versa. This study unifies the concepts of the RCC and RPM and shows that these concepts are not limited only to large rivers, but are applicable to small southern temperate rivers too. However, some tenets of the theoretical models were challenged. For example, it challenges the proposition by the RCC that the fine particulate organic matter leaked from upstream breakdown of coarse particulate organic matter is predominantly allochthonous. Additionally, this study showed that in the headwaters, the RPM underestimated the role of autochthony. Overall, the results showed that the Kowie River and its riparian area are intrinsically connected. Once we understand the mechanisms controlling connections and subsidies across ecotones, we can then start to predict the consequences of disruptions to these connections by climate change and/or land use changes. To make predictions about future perturbations to rivers and riparian zones, studies like this, which considers the form and magnitude of subsidies, are needed to provide baseline information. Algal resources (e.g. epiphyton), macrophytes, riparian plants, terrestrial organisms and aquatic organisms all contributed to aquatic and terrestrial linkages in the Kowie River; therefore, it is important to conserve the different components of these ecosystems.
Keywords: Uncatalogued